Presentation. New capitalisms and territorial transformations in the Andean region - Baud, Michiel; Boelens, Rutgerd; Damonte, Gerardo (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
This presentation introduces a special issue that analyzes the new territorial configurations taking shape in the Andean region under the developmentalist governments of the 21st century. The new territorial projects seek to increase the extraction of resources, the transference of crucial products on local level, and economic development. This remodeling transforms the techno-natural, cultural and political orders and creates new ‘capitalisms’ that facilitate knowledge production on, exploitation of, and control over local societies. This special issue analyzes the practical and political expressions of these new forms of social and ecological (re)territorialization.